Socialization of ARI Towards Environmental Factors in Lorejo Village, Bakung District, Blitar Regency - Setyo Budi Susanto; Shalma Adeesya Al'Rahma; Cindy Qaula Agustin; Aditya Bagas Prayoga (Universitas STRADA Indonesia, 2024)
Based on the results of Riskesdas (2018), the prevalence of ARI in Indonesia is 9.3%, of which 9.0% are male and 9.7% are female (Ministry of Health of the Republic of Indonesia, 2018). This understanding has not been fully understood by mothers and the elderly, so it is necessary to conduct socialization regarding the understanding and causes of people getting ARI. Selection of Dsn. Ngebruk Ds. Lorejo Kec. Bakung Kab Bitar, because the mobility of the community lacks knowledge about ARI and to increase insight regarding environmental factors that are at risk of ARI (Acute respiratory tract infection). The type of research used is descriptive analytical and the research design is cross-sectional. The objects of this study were mothers and elderly people studying in Ngebruk hamlet, Lorejo village, Bakung sub-district, Blitar regency. The results of ARI knowledge were obtained as much as 73.33% using the Gutman scale approach. With these results, it is stated that participants' knowledge of ARI is good, but participants still need to increase their knowledge in order to reduce the risk of contracting ARI. The results of ARI knowledge of 90%, with the results before and after the provision of community service materials increasing. It is important to have community service on preventing ARI in Lorejo Village, because this is very continuous with the priority of health problems in Lorejo Village, namely the counseling method that is less creative and innovative. By providing knowledge about understanding and also preventing ARI for mothers and the elderly, it is hoped that they can independently apply what they have learned to their families.